Thermoelectric properties of polycrystalline palladium sulfide. Issue 24 (9th April 2018) - Chen, Liu-Cheng; Jiang, Bin-Bin; Yu, Hao; Pang, Hong-Jie; Su, Lei; Shi, Xun; Chen, Li-Dong; Chen, Xiao-Jia
Abstract : Measurement of the electrical, thermal, and structural properties of palladium sulfide (PdS) has been conducted in order to investigate its thermoelectric performance. Abstract : Measurement of the electrical, thermal, and structural properties of palladium sulfide (PdS) has been conducted in order to investigate its thermoelectric performance. A tetragonal structure with the space group P 42 / m for PdS was determined from X-ray diffraction measurement. The obtained power factor of 27 μW cm −1 K −2 at 800 K is the largest value obtained for the transition metal sulfides studied so far. The maximum value of the dimensionless figure of merit is 0.33 at 800 K. These results indicate that binary bulk PdS has promising potential for good thermoelectric performance.